Association of Adipose Tissue Distribution With Type 2 Diabetes in Breast Cancer Patients. (November 2020) - Qi, Jia; Hu, Hui; Yaghjyan, Lusine; An, Lejun; Kalim, Harris A; Cooke, Erinn O; Cheng, Ting-Yuan David
Purpose: We examined the association of adipose tissue distribution with type 2 diabetes (T2D) in breast cancer patients. Methods: Participants (N = 238) diagnosed with breast cancer at 20-75 years old who received breast cancer treatment at a major hospital from January 1, 2012, to December 31, 2017, with at least one completed and identifiable abdominal or pelvic computed tomography (CT) scan and data regarding race and ethnicity were included. Thirty-two breast cancer patients were identified as T2D patients after their breast cancer diagnoses. The adipose tissue distribution (visceral fat area [VFA], subcutaneous fat area [SFA], and the ratio of VFA to SFA [VFA/SFA]) was quantified on CT images of the third lumbar vertebra. T2D status was retrieved from patients' electronic medical records. The association of adipose tissue distribution with T2D in women with breast cancer was examined using multivariable logistic regression. Results: Participants with T2D had significantly smaller SFA compared to those without T2D (odds ratio [OR] = 0.88, 95% confidence interval [95% CI] = 0.81-0.96, per 10 cm 2 SFA). A positive association of VFA/SFA ratio with T2D was observed (OR = 19.57, 95% CI = 3.26-117.42, per unit VFA/SFA), although the estimate was imprecise. Conclusions: The amount of subcutaneous adipose tissue was inversely associated with T2D, and the ratio of the amount of visceral adipose tissue to the amount of subcutaneous adipose tissue was positively associated with T2D in breast cancer patients.